The use of Annona squamosa seed, leaf and bark as an alternative in the control of Cryptotermes brevis (Research, Society and Development, 2021)
The changes in human behavior towards the environment, the disorderly urban development, globalization and climate change are some of the factors that promote the occurrence and spread of pests that somehow bring damage. This occurrence is aimed at termites, which are insects known for their habit of feeding on cellulose, that is, papers, books, and wooden structures, causing accidents. Cryptotermes brevis are a major cause of damage to various wood species commonly used throughout the country, which cause major public health problems. Annonaceae have been extensively investigated because they present many species as a source of insecticidal compounds with different modes of action on insects. Therefore, this work aims to develop a natural, economical and sustainable product by using the extracts of the seeds of the fruit of the earl (Annona squamosa) as a resource to combat dry wood termites. From the results, it was possible to prove the veracity of the hypothesis that the natural insecticides developed from the extract of the seeds of the fruit of the earl (Annona squamosa) are very efficient, and are effective in the issue of mortality rates of Cryptotermes brevis.